2009
DOI: 10.1084/jem.20081811
|View full text |Cite
|
Sign up to set email alerts
|

CD4+ regulatory T cells require CTLA-4 for the maintenance of systemic tolerance

Abstract: Cytotoxic T lymphocyte antigen-4 (CTLA-4) plays a critical role in negatively regulating T cell responses and has also been implicated in the development and function of natural FOXP3+ regulatory T cells. CTLA-4–deficient mice develop fatal, early onset lymphoproliferative disease. However, chimeric mice containing both CTLA-4–deficient and –sufficient bone marrow (BM)–derived cells do not develop disease, indicating that CTLA-4 can act in trans to maintain T cell self-tolerance. Using genetically mixed blasto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
166
0
6

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 237 publications
(179 citation statements)
references
References 71 publications
7
166
0
6
Order By: Relevance
“…A decreased CTLA-4 expression level was previously described in activated cells [21,22], and it is known that CTLA-4 is essential for initial Treg in vivo suppressor activity on APCs [23,24]. According to our results, we suggest that rapid CTLA-4 internalization occurs in Tregs at the moment of contact with APCs, suppressing the expression of MHC II and/or B7 molecules on the later.…”
Section: Discussionsupporting
confidence: 81%
“…A decreased CTLA-4 expression level was previously described in activated cells [21,22], and it is known that CTLA-4 is essential for initial Treg in vivo suppressor activity on APCs [23,24]. According to our results, we suggest that rapid CTLA-4 internalization occurs in Tregs at the moment of contact with APCs, suppressing the expression of MHC II and/or B7 molecules on the later.…”
Section: Discussionsupporting
confidence: 81%
“…However, the response in the absence of Treg cells is comparable in magnitude to the response observed when only CTLA-4 interactions were blocked. This is of particular interest in the light of experiments demonstrating a crucial role of CTLA-4 in the suppressive function of Treg cells (22)(23)(24)(25). (20,27), up-regulate IL-10 (28) and the coinhibitory molecule B7-H3, and are compromised in the stimulation of naive T cells (27).…”
Section: Discussionmentioning
confidence: 99%
“…These results confirmed that the Ctex/Cd3z locus controls CTLA-4 expression in CD4 + and CD8 + T cells and restricted the region of interest to 28.8 Mb. CTLA-4 plays an important role in the function of CD4 + CD25 + Foxp3 + regulatory T cells (28)(29)(30); therefore, we specifically analyzed the expression of CTLA-4 in this subset. A significantly lower frequency of Foxp3 + T cells expressed CTLA-4 in NOD compared with B6 mice (Fig.…”
Section: Defective Expression Of Cd3z and Ctla-4 In Nod T Cells Aftermentioning
confidence: 99%